Special Needs in the Early Years: Snapshots of practice - Wolfendale, Sheila (Routledge, 2000)
This book celebrates good practice in the area of early years and special needs by bringing together authors who are either practitioners or researchers, from a range of different and diverse early years settings including nurseries and units providing special provision. They describe their work with young children who have different and distinctive special needs and disabilities.